2024
DOI: 10.34133/bmef.0038
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Synthetic Delivery Formulations for Peptide-Based Cancer Vaccines

Kefan Song,
Suzie H. Pun

Abstract: With the recent advances in neoantigen identification, peptide-based cancer vaccines offer substantial potential in the field of immunotherapy. However, rapid clearance, low immunogenicity, and insufficient antigen-presenting cell (APC) uptake limit the efficacy of peptide-based cancer vaccines. This review explores the barriers hindering vaccine efficiency, highlights recent advancements in synthetic delivery systems, and features strategies for the key delivery steps of lymph node (LN) drainage, APC delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 144 publications
0
0
0
Order By: Relevance
“…These mice express a hybrid major histocompatibility complex (MHC) molecule containing the extracellular α-1 and α-2 domains of the human HLA-A*02 receptor and the transmembrane and cytoplasmic domains of murine H-2D d . We used the subcutaneous route for vaccination because it facilitates high accumulation of nanoparticles in the lymph nodes and enables prolonged release of vaccine cargo, thereby enhancing immune responses. , Additionally, our previous studies observed the sufficient induction of T-cell response using this route. ,,, The mice were vaccinated every 2 weeks for three total injections with 6 nmol CpG 1826 (a murine TLR9 agonist) oligonucleotide and E7 11–19 peptide in the form of either an additive simple mixture in PBS (E7 Admix), or a liposomal SNA encapsulating the peptide antigen and functionalized with CpG DNA containing a 3′ hydrophobic cholesterol or (C12) 9 anchor (Figure A).…”
mentioning
confidence: 99%
“…These mice express a hybrid major histocompatibility complex (MHC) molecule containing the extracellular α-1 and α-2 domains of the human HLA-A*02 receptor and the transmembrane and cytoplasmic domains of murine H-2D d . We used the subcutaneous route for vaccination because it facilitates high accumulation of nanoparticles in the lymph nodes and enables prolonged release of vaccine cargo, thereby enhancing immune responses. , Additionally, our previous studies observed the sufficient induction of T-cell response using this route. ,,, The mice were vaccinated every 2 weeks for three total injections with 6 nmol CpG 1826 (a murine TLR9 agonist) oligonucleotide and E7 11–19 peptide in the form of either an additive simple mixture in PBS (E7 Admix), or a liposomal SNA encapsulating the peptide antigen and functionalized with CpG DNA containing a 3′ hydrophobic cholesterol or (C12) 9 anchor (Figure A).…”
mentioning
confidence: 99%